Analysis of solidification microstructure and hot ductility of Fe–22Mn–0·7C TWIP steel. (November 2014) - Lan, P.; Song, L.; Du, C.; Zhang, J.
<x content-type="archive" xml:space="preserve">Abstract</x> The characteristics and evolution of the solidification microstructure of a Fe–0·7C–22Mn (wt-%) TWIP steel was experimentally analysed. The primary dendrite arm space was about 1–2 mm while the diameter of equiaxed grains was about 2–4 mm. Decreasing the Mn concentration was proved beneficial to grains refinement and interdendrite soundness improvement. The tensile strength and yield strength of the concerning TWIP steel were found to be higher than that of C–Mn HSLA steel under as cast conditions above 1073 K, according to the comparison of hot tensile experiment results. It is inferred the solution strengthening effect should be the main explanation for that. The hot ductility of this TWIP steel was observed to be not very favourable, since most of the reduction rates of area were lower than 40%. Obvious drop of the hot ductility within the temperature range from 1073 to 1223 K of this Fe–0·7C–22Mn TWIP steel was determined. Intragranular MnS inclusions and grain boundaries sliding at elevated temperatures should be the main reason, according to the experimental results of optical microscope (OM), scanning electron microscope (SEM) and X-ray diffraction (XRD). Besides, both strength and ductility increased linearly as logarithmic strain rate increased, attributed to the combined effect of strain hardening, dynamic strain aging and dynamic recrystallisation.